Benchmarking MySQL and NoSQL Databases on Egovbench Application - Nur Aini Rakhmawati; Muhammad Zuhri; Radityo Prasetianto Wibowo; Anwar Romadhon; Herdy Ardiansyah; Olive Khoirul (Journal of Information Technology and Its Utilization, 2019)
E-Government is a result of technological advances in the government field. E-government assessment is needed to encourage the development of e-government in a better direction. The e-Government assessment can be measured using the Egovbench application. Egovbench performs crawling to obtain information from related websites or social media. The process of crawling done by Egovbench produces extensive data, which reduced performance in data processing. Therefore, there is a need for a database solution that has the best performance such as high processing speed and small database size. This study examined the comparison between relational databases and non-relational databases based on selected metrics to obtain the most suitable database solution for Egovbench. The results show that the MySQL database has the advantage of complex query processing and the use of the database with the smallest storage space. MongoDB database has the advantage of low data transfer volumes. Couchbase database has the advantage of short and straightforward query processing with a high number. The evaluation results show that MySQL is more suitable for Egovbench needs, which is the best response time and query per second. MySQL outperformed the other two databases on backup and storage file sizes testing.